A preliminary survey of the Karaoğlan Hill archaeological site - Sharif, L . Jaza Shorsh Hama; Qadir, Zana Abdul Karim (Sulaimani Journal for Humanities, 2025)
Karaoglan Hill is one of the monuments of Kufri township, the second settlement after the bear of Kufri. This monument is located in the southeast of Kufri city. It consists of two main hills The first hill is a larger archaeological hill with a height of about (5) m and an area of about 1 km2, on the surface of both hills and the monument in general a large number of various pieces of clay. In this paper we try to present the archaeological history of Karaoğlan based on the sources available about the study area with the archaeological evidence obtained during the survey of the site such as (architecture and clays).